2018
DOI: 10.1016/j.cmet.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Serine Synthesis via PHGDH Is Essential for Heme Production in Endothelial Cells

Abstract: The role of phosphoglycerate dehydrogenase (PHGDH), a key enzyme of the serine synthesis pathway (SSP), in endothelial cells (ECs) remains poorly characterized. We report that mouse neonates with EC-specific PHGDH deficiency suffer lethal vascular defects within days of gene inactivation, due to reduced EC proliferation and survival. In addition to nucleotide synthesis impairment, PHGDH knockdown (PHGDH) caused oxidative stress, due not only to decreased glutathione and NADPH synthesis but also to mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
150
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(158 citation statements)
references
References 47 publications
(85 reference statements)
7
150
1
Order By: Relevance
“…Previous studies have shown that PHGDH is highly expressed in radial glial cells, antitumor CD8+ T-cells, astrocytes, macrophages, and endothelial cells. 52,59 Humans with hypomorphic mutations in PHGDH exhibit developmental delay and mental retardation, both of which can be ameliorated by serine supplementation, suggesting that transitory PHGDH inhibition following completion of neuronal development may be tolerable. While our study found no evidence of neurotoxicity and weight loss due to PHGDH inhibition, future studies will be needed to determine whether PHGDH inhibition needs to be staggered with therapies that require functional PHGDH-dependent cells, such as cytotoxic CD8+ T-lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that PHGDH is highly expressed in radial glial cells, antitumor CD8+ T-cells, astrocytes, macrophages, and endothelial cells. 52,59 Humans with hypomorphic mutations in PHGDH exhibit developmental delay and mental retardation, both of which can be ameliorated by serine supplementation, suggesting that transitory PHGDH inhibition following completion of neuronal development may be tolerable. While our study found no evidence of neurotoxicity and weight loss due to PHGDH inhibition, future studies will be needed to determine whether PHGDH inhibition needs to be staggered with therapies that require functional PHGDH-dependent cells, such as cytotoxic CD8+ T-lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Heme and heme-containing enzymes play a significant role in this process, but the linkage between these phenomena has not been extensively explored. Serine synthesis deficiency induced heme depletion in ECs and caused decreased mitochondrial respiration and multiorgan angiogenic defects in animals (Vandekeere et al, 2018), while heme accumulation in ECs due to an altered heme exporter affects angiogenesis and causes endoplasmic reticulum stress (Petrillo et al, 2018). Apart from ECs, nonsmall cell lung carcinoma cells with elevated heme synthesis levels had increases in enzyme activities of the ETC.…”
Section: Discussionmentioning
confidence: 99%
“…Severe heme depletion could possibly disrupt NADH/H + and redox homeostasis, as already evident from ETC dysfunction. Moreover, increased ROS levels in ECs can shift their metabolic needs to accommodate cellular damage and dysfunction, in which case both cellular energetic systems are collapsed (Vandekeere et al, 2018;Warren et al, 2014;Wellen and Thompson, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, SFXN1 is a constituent of the 442 mitochondrial heme metabolon (Medlock et al, 2015). In endothelial cells, depletion of cellular 443 serine by deletion of PHGDH, encoding the rate-limiting enzyme in de novo serine biosynthesis, 444 results in inadequate heme and impedes OXPHOS capacity (Vandekeere et al, 2018). In our 445…”
Section: Loss Of Sfxn1 Causes Complex Iii-related Defectsmentioning
confidence: 95%